Didactic Design of Lesson Study-based Microteaching Learning for Prospective Mathematics Teacher Students - Sukmawati, Rika; Purbaningrum, Kus Andini (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2021)
The basic objective of the microteaching course is to support the implementation of apprenticeship 3 (teaching practice) in the seventh semester at school. So far, the practice of teaching in the classroom by students is often constrained by the readiness of students in preparing these teaching tools. To overcome these obstacles, it is necessary to design a didactic condition according to the obstacles experienced by students, to be able to guide students in carrying out teaching practices properly. This process requires planning (plan), implementation (do), and reflection (reflection) of learning so that the microteaching learning process is carried out based on lesson study. The purpose of this study was to develop a didactic design in microteaching learning for lesson study-based mathematics teacher candidates. The research method used is qualitative in the form of didactic design research. Based on the implementation of the didactic design of lesson study-based microteaching learning for prospective mathematics teacher students, it is concluded that this didactic design can be used as alternative learning to overcome the learning obstacles experienced by students in microteaching learning.Tujuan dasar dari mata kuliah microteaching adalah untuk mendukung pelaksanaan magang 3 (praktek mengajar) pada semester VII di sekolah. Sejauh ini, praktik mengajar di kelas yang dilakukan mahasiswa sering terkendala oleh kesiapan mahasiswa dalam mempersiapkan perangkat pengajaran tersebut. Untuk mengatasi hambatan tersebut, perlu dirancang suatu kondisi didaktis sesuai hambatan yang dialami mahasiswa, agar mampu membimbing mahasiwa dalam melaksanakan praktik mengajar dengan baik dan benar. Proses tersebut membutuhkan perencanaan (plan), implementasi (do) dan refleksi (reflection) pembelajaran, sehingga proses pembelajaran microteaching dilakukan berbasis lesson study. Tujuan penelitian ini adalah untuk mengembangkan desain didaktis pada pembelajaran microteaching bagi mahasiswa calon guru matematika berbasis lesson study. Metode penelitian yang digunakan adalah metode kualitatif berupa penelitian desain didaktis. Berdasarkan implementasi desain didaktis pembelajaran microteacing berbasis lesson study pada mahasiswa calon guru matematika disimpulkan bahwa desain didaktis ini dapat digunakan sebagai alternatif pembelajaran untuk mengatasi hambatan belajar yang dialami mahasiswa pada pembelajaran microteaching.